The Effectiveness of Group Rational Emotive Behavior Therapy to Reduce Student Learning Burnout - Cony Anggreini; Daharnis Daharnis; Yeni Karneli (Universitas Negeri Padang, 2019)
This study aims to examine the effectiveness of the Group Rational Emotive Behavior Therapy approach in reducing learning burnout experienced by students due to irrational thoughts. This research is a quantitative analysis that uses the method of Quasi-Experiment through the design of The Non-Equivalent Control Group. The subjects in this study were class VIII-1 students as the experimental group and class VIII-8 students as the control group. The instrument used is a learning burnout scale with the validity of 0.273 (Pearson Product Moment) and reliability of 0.936 (Alpha Cronbach). Data analysis was conducted using nonparametric statistics with the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov 2 Independent Samples. The results of this study show that the REBT approach in a group setting is effective for reducing student learning burnout. This can be seen from the score of student learning burnout in the experimental group, which experienced a greater and more significant decline than the control group.